O uso do osciloscópio: uma revisão bibliográfica - Santos, Pablo Adriel Alves dos (Universidade Federal Rural do Semi-Árido, 2020)
In this work, a bibliographic review of the oscilloscope is performed as an instrument for measuring electrical and audible signals. The importance of this equipment is presented in the description and analysis of systems studied in Electronics and Physics, discussing historical aspects, operability, and the existing distinction between analog and digital instruments. In addition, it points out in the study some alternatives, already present in the literature, to conventional oscilloscopes, commonly used in higher education institutions. Through this study it was possible to observe that, currently, there are a range of possibilities of instruments capable of analyzing electrical and sound signals. It is understood that a greater knowledge about these devices can be a way to improve accessibility in terms of experimental studies of electrical and sound phenomena.
Monografia
Keywords: Revisão bibliográfica; Osciloscópio; Sinais elétricos; Sinais sonoros; Literature review; Oscilloscope; Electrical signals; Sound signals; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA